(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Salamanes JJDP, Santos JMJ, Austria ES, Villancio GGS. 2022. Short Communication: A new species of tarantula of the genus Orphnaecus Simon, 1892 (Araneae: Theraphosidae) from the Province of Dinagat Islands, Philippines. Biodiversitas 23: 4283-4288. Orphnaecus adamsoni sp. nov., a new species of tarantula of the genus Orphnaecus Simon, 1892 is described and illustrated based on the specimens collected from the Province of Dinagat Islands, Philippines. It closely resembles O. kwebaburdeos (Barrion-Dupo, Barrion & Rasalan, 2015). However, it can be easily distinguished by having a rounded carapace, shorter leg segments, more clavate-paddle shaped maxillary lyra, and a different habitat. This mygalomorph spider discovery constitutes the fifth species described for Orphnaecus and the fourth record in the Philippines.